1982
DOI: 10.1002/ajh.2830120209
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and sites of destruction of 111indium‐oxine‐labeled platelets in idiopathic thrombocytopenic purpura: A quantitative study

Abstract: Kinetics and quantification of the sites of destruction of 111-Indium-oxine-labeled autologous platelets were investigated in eight patients with idiopathic thrombocytopenic purpura. The mean platelet count was 17 +/- 9 X 10(9)/liter; platelets were separated by differential centrifugation and labeled with 5.6 +/- 2.5 MBq 111In. Whole body and organ 111In-platelet distribution was quantitated with a scintillation camera and a computer-assisted imaging system acquisition matrix. Areas of interest were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(18 citation statements)
references
References 19 publications
0
15
0
3
Order By: Relevance
“…However, autologous platelet survival studies in the 1980s, showing that most ITP patients had normal or decreased platelet turnover, suggested that platelet production in chronic ITP may also be impaired. [3][4][5][6] This hypothesis is supported by early morphologic studies of ITP bone marrow showing normal or increased numbers of megakaryocytes with a shift to younger forms that lacked evidence of cytoplasmic granularity or platelet formation and manifested degenerative changes in the nucleus and cytoplasm. 13,14 Subsequent studies, using electron microscopy, showed 50% to 75% of ITP megakaryocytes had extensive damage consisting primarily of abnormalities of the demarcation membrane system.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…However, autologous platelet survival studies in the 1980s, showing that most ITP patients had normal or decreased platelet turnover, suggested that platelet production in chronic ITP may also be impaired. [3][4][5][6] This hypothesis is supported by early morphologic studies of ITP bone marrow showing normal or increased numbers of megakaryocytes with a shift to younger forms that lacked evidence of cytoplasmic granularity or platelet formation and manifested degenerative changes in the nucleus and cytoplasm. 13,14 Subsequent studies, using electron microscopy, showed 50% to 75% of ITP megakaryocytes had extensive damage consisting primarily of abnormalities of the demarcation membrane system.…”
mentioning
confidence: 49%
“…[3][4][5][6] Because megakaryocytes express GPIIb-IIIa and GPIb-IX on their surfaces during maturation 7 and because most ITP autoantibodies react with one or both of these glycoprotein complexes, 8,9 it follows that autoantibody binding to megakaryocytes could interfere with platelet production and release from the bone marrow either by causing intramedullary megakaryocyte or platelet destruction or by interfering with megakaryocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
“…5,9 The modulation of PLTs, however, is less characterized. The splenic MPS plays important roles in the phagocytic clearance of PLT during ITP, 1,10,11 suggesting that the severity of ITP is associated with PLT-phagocyte engagements. Thus, we established a flow cytometry-based PLT-splenic CD14 ϩ leukocyte (PLT-CD14 ϩ LC) engagement analysis to investigate the roles of PLTs and phagocytes in IVIg-primed DCs (IVIg-DCs)-mediated modulations.…”
mentioning
confidence: 99%
“…In autoimmune hemolytic anemia, the compensatory reaction is much more pronounced, except when circulating antibodies are directed to normoblasts [31]. Previous studies have shown that, in the majority of ITP patients, the PPR is either reduced or normal [28,30,[32][33][34][35][36]. Additional support for a suppressed platelet production in ITP comes from in vitro studies showing that megakaryocyte production and maturation can be inhibited by antiplatelet antibodies [1,2,37].…”
Section: Discussionmentioning
confidence: 99%